Prospects for the development of inclusive entrepreneurship for demobilized servicemen in Ukraine (Economics and region, 2024)
This article examines the current challenges and opportunities facing demobilized military personnel in the context of entrepreneurship. The article focuses on the fact that the growth of inclusive entrepreneurship is an important tool for the socio-economic adaptation of veterans, as it not only contributes to their integration into civil life, but also has the potential to stimulate the development of the country's economy. The study begins with an analysis of existing government programs that support veterans in their entrepreneurial endeavors, such as access to financing, training courses, and consulting services. It was found that, despite the existence of programs, insufficient popularization and limited access to them remain significant obstacles. However, the growing attention to the problems of veterans on the part of society and the state creates potential for the development of new initiatives in this area. The article pays special attention to the challenges that arise on the way to creating a successful business, including social, psychological and economic factors. It has been found that many demobilized servicemen face difficulties in adapting to civilian life, which can make it difficult for them to pursue entrepreneurship. However, with the right support and training, veterans can become successful entrepreneurs using their skills and experience. The final part of the article formulates recommendations for state structures, business and public organizations regarding the creation of a favorable environment for the development of inclusive entrepreneurship. It is proposed to integrate veterans into training and mentoring programs, provide access to financial resources and intensify cooperation between different sectors of society. Thus, the article emphasizes the importance of the development of inclusive entrepreneurship for demobilized servicemen in Ukraine as a key element of their socio-economic adaptation, which requires a comprehensive approach and attention from all interested parties.
Keywords: inclusive entrepreneurship; demobilized servicemen; social adaptation; reintegration; economic support; veteran business; interdisciplinary support